2011
DOI: 10.1007/s10584-011-0055-3
|View full text |Cite
|
Sign up to set email alerts
|

‘Low carbon’ metals, markets and metaphors: the creation of economic expectations about climate change mitigation

Abstract: Dealing with the threat of anthropogenic climate change has been a challenge for policy makers for a long time. In recent years, the problems posed by climate change and solutions proposed to mitigate its effects have been framed by lexical 'carbon compounds', such as carbon footprint or carbon trading and by one dominant metaphor, the market metaphor. Through a detailed content analysis of industry and press coverage from 1985 to the present, this paper examines the fate of one important lexical compound in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…[ii] A day after the budget, on 23 April, newspapers reported that Ed Miliband, the then Secretary of State for Energy and Climate (another important source of media announcements at that time), had proclaimed that up to four new coal-fired power plants would be built only on the condition that they be fitted with CCS facilities. This announcement referred, like so many at the time, to building a "low carbon future" (Nerlich, 2011) and stopping dangerous climate change. Again reference is made to UK leadership in CCS.…”
Section: -2012mentioning
confidence: 91%
“…[ii] A day after the budget, on 23 April, newspapers reported that Ed Miliband, the then Secretary of State for Energy and Climate (another important source of media announcements at that time), had proclaimed that up to four new coal-fired power plants would be built only on the condition that they be fitted with CCS facilities. This announcement referred, like so many at the time, to building a "low carbon future" (Nerlich, 2011) and stopping dangerous climate change. Again reference is made to UK leadership in CCS.…”
Section: -2012mentioning
confidence: 91%
“…"Going green", for example, is a widely used metaphor signalling adoption of climate-friendly political positions, participation in climate-friendly practices and advocacy for the adoption of such practices (Bevitori 2011;Dobrin 2010). "Green" in its metaphorical sense features regularly in arguments exploring the business opportunities presented by climate change as in discussing the therapeutic but also economic gains from "green medicine" (Väliverronen and Hellsten 2002) or explaining how industries from mining and metallurgy to car manufacturing can increase their profits by "turning green into gold" (Nerlich 2012). The metaphorical term "Green New Deal" was widespread in use in the aftermath of the 2008-2009 global financial crisis to refer to economic stimulus packages that would include significant climate-friendly investments (Feindt and Cowell 2010).…”
Section: Colour Metaphorsmentioning
confidence: 99%
“…Koteyko and Brigitte Nerlich use the tools of "corpora linguistics" or "corpus linguistics" -a computer-assisted method of collecting and tracking instances of words in texts to derive abstract rules by which language functions -to track carbon compounds, conceived linguistically rather than chemically (Koteyko 2010;Nerlich 2012). Their studies offer an explicit engagement with the public spaces in which these novel carbon compounds occur as profoundly important political sites:…”
Section: Discursive Carbon Compoundsmentioning
confidence: 99%